The Concept of Ijtihad as a Method of Renewing Ibn Taimiyah's Islamic Law - Umar, Marzuki (Jurnal Al Tasyri'iyyah, 2021)
Islamic law is a law based on the Qur'an, hadith, qiyat and ijma'. In essence, Islamic law is used as the basis of life and solutions to human problems. However, at present, the diversity of problems faced by humans makes Islamic law seem rigid and too binding. This paper will explain the concept of Ijtihad by Ibn Taimiyah in the context of reforming Islamic law. This research is in the form of library research through content analysis techniques. The main sources used by Ibn Taimiyah in performing ijtihad are the Qur'an and hadiths. He never put reason as a basis for thinking because for him reason is weak and weakens belief in the religion of Allah. In addition, he carried out Ijtihad by providing comparisons between existing schools and trying not to influence anyone because the method of ijtihad he did was ijtihad independently. The results of ijtihad produced by Ibn Taimiyah which are currently used are the requirements for the implementation of prostration and recitation as well as the exchange of unproductive waqf assets.Keywords: Islamic Law; Ibnu Taimiyah; Ijtihad